The Traditional Intramedullary Axis Underestimates the Medial Tibial Slope Compared to Transmalleolar Sagittal Axis in Image-based Robotic-Assisted Unicompartimental Knee Arthroplasty - Chirico, Mattia; Zanna, Luigi; Akkaya, Mustafa; Carulli, Christian; Civinini, Roberto; Innocenti, Matteo (The Journal of Knee Surgery, 2024)
The medial unicompartmental knee arthroplasty (mUKA) has been recognized as an excellent treatment for medial knee osteoarthritis. The posterior tibial slope (PTS) is measured radiographically with the intramedullary axis (IMA) to the tibial baseplate on the sagittal plane radiograph. However, in most computer-navigated or robotic mUKAs, the PTS is set from a transmalleolar axis (TMA).The PTS difference was evaluatedbetween the sagittal TMA and the sagittal IMA of patients undergoing a CT-based primary robotic-assisted mUKA.We retrospectively reviewed the preoperative computed tomography (CT) scans taken according to the MAKO system protocol (Stryker) of 67 patients undergoing mUKAs. We measured the angular difference between the IMA and the TMA in the sagittal plane.Using the TMA to set the PTS the estimation of the slope of the medial tibial plateau would increase by an average of 1.9 ± 3.2 degreescompared to the IMA. Furthermore, in nineknees, PTS was decreased.Tibial components implanted with the help of a CT scan-based preoperative planning MAKO will show an average of 1.9 degrees more than those measured on sagittal radiographs potentially of concern for knee kinematics. A universal language is needed to standardize the slope calculation and the respective reference axis used.
Keywords: mUKA; slope; knee; unicompartmental knee arthroplasty; robotic-assisted